Uso do ultrassom em sal e aplicação em peito de frango - Silva, Sarah Bianca Soares da (2020)
Salt is present daily in the diet as an ingredient in most processed foods and its high consumption is related to some diseases. The daily consumption of Brazilians exceeds 5 grams of the limit indicated by the World Health Organization. Aiming to seek an alternative to reduce daily salt consumption, the work aims to modify the morphology of conventional salt, with different granulometries, with the application of the ultrasound to increase the salty flavor intensity, and thus reducing the amount of salt added daily in industries and households. Research currently carried out indicates that ultrasound is a promising methodology and guarantees beneficial modifications for products and by-products in the industry. In this work, four salts were treated by ultrasound at 40kHz, barbecue (coarse), special (common), granulated and microsal salt. These treated and untreated salts were analyzed by optical microscopy, where the granules showed several changes in both structure and size. Subsequently, these salts were added in half a chicken breast where analysis of the physico-chemical and technological characteristics, histological evaluation, microbiological analysis, according to the legislation, sodium analysis and sensory analysis of the chicken breast half occurred. Measurements were performed and compared with the tukey test, to verify if there was a difference between the samples. The results found indicated that the application of the salt did not cause significant difference between the majority of the samples in the physicochemical, technological characteristics. Some salts showed better changes in morphology, positive results in sensory analysis and reduction in the amount of sodium, thus indicating that the use of ultrasound in salt can result in the reduction of sodium in half a chicken breast without causing negative effects on the sensory by consumers.